Sink into the Epigenome: Histones as Repositories That Influence Cellular Metabolism. (September 2018) - Ye, Cunqi; Tu, Benjamin P.
Abstract : Epigenetic modifications on chromatin are most commonly thought to be involved in the transcriptional regulation of gene expression. Due to their dependency on small-molecule metabolites, these modifications can relay information about cellular metabolic state to the genome for the activation or repression of particular sets of genes. In this review we discuss emerging evidence that these modifications might also have a metabolic purpose. Due to their abundance, the histones have the capacity to store substantial amounts of useful metabolites or to enable important metabolic transformations. Such metabolic functions for histones could help to explain the widespread occurrence of particular modifications that may not always be strongly correlated with transcriptional activity. Highlights: Histone methylation and acetylation are sensitive to metabolic states. Histone methylation consumes SAM, enabling histones to function as a methyl sink. Histone acetylation deposits acetyl units as a source of acetate. 'Bulk' histone methylation and acetylation might reflect these metabolic functions.